The Sad Case of Porto Rico - Muñoz Marín, Luis (My University, 1929)
The Sad Case of Porto Rico The American Mercury vol. XVI, num. 62 (Feb,1929)
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.